Sustainable Dry Land Farming Development Through Integration of Crops and Bali Cattle in North Lombok District, from an Ontological Perspective - Yusuf, M.; Sahidu, Arifuddin; Sarjan, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This aims of this research are to: (1) Analyze the concept and importance of the Balinese system of crop and livestock integration in rainfed agriculture from an ontological perspective and its impact on the environment, (2) Analyze the conceptual framework and importance of the Balinese system of crop and livestock integration in dryland agriculture from an ontological perspective; (3) Formulate a strategy to develop rainfed agriculture in North Lombok Regency. The method used is the study of the literature. Data analysis uses qualitative descriptive methods and ontological analysis to understand the nature of system integration. The research results show that: (1) An ontological understanding of the Bali livestock crop integration system provides a comprehensive conceptual framework for the development and implementation of a sustainable system, with a fundamental understanding of the nature of the integration system which is holistic. System that combines biological components, based on the principle of matter and energy cycles, and reflects the unity of ecological function and socioeconomic function. It is very important to develop the integration of crops and livestock because it can be a solution to problems in regional development; (2) Rainfed agriculture in northern Lombok Regency has great development potential, but still faces several technical, economic and social obstacles; (3) Strategy to develop rainfed agriculture in KLU, which includes: (a) Technical production strategy, (b). Socioeconomic strategy; (c) Technological ttrategy, (d) Institutional strategy